Diversity combining adaptive antenna array for a land mobile satellite terminal - Beach, M; Swales, S; McGeehan, J; Edwards, D (Publ by IEE, 1989)
In this paper the proposal for a Diversity Combining Antenna Array for a land mobile satellite (LMS) terminal is further examined by the authors. This novel approach employs established diversity combining techniques previously developed for mobile terrestrial radio. Here it is suggested that a diversity based receiver architecture would allow the coherent recombination of the multipath signal energy present at the mobile terminal site, thereby enhancing system performance for a given link budget. In order to justify this new approach to terminal design it has been necessary to obtain additional propagation measurements of the land mobile satellite channel and these results are presented here. Finally, the implementation of such a transceiver is briefly addressed.